Transformative Leadership Model in Academic Supervision in the Era of Flipped Classroom and Hybrid Learning - Nani Septiana; Istianatul Imamah; Lely Ana Ferawati Ekaningsih (proceedings.icesy, 2026)
This study aims to analyze and develop an optimization model for lecturer academic supervision based on transformational leadership within the context of Flipped Classroom and Hybrid Learning implementation. A qualitative case study was conducted in the Islamic Education Management Master's program at KH. Mukhtar Syafaat University, Banyuwangi. Data were collected through in-depth interviews with program leaders, lecturers, and staff; non-participant observation; document analysis; and reflection session audio analysis. Data were analyzed using an interactive model with triangulation techniques. The results reveal three main findings: (1) technology integration via a Learning Management System (LMS) enhances feedback objectivity and speed; (2) a participatory-appreciative supervision approach fosters two-way reflection that motivates pedagogical innovation; and (3) strengthening professional learning communities reinforces collaborative and collective innovation. The study concludes that the developed model shifts the supervision paradigm from an evaluative function to a strategic mentorship adaptive to digital pedagogy. Thus, it can be adopted by higher education leaders to enhance supervision effectiveness and the success of innovative learning.